The Consequences of Corruption: Evidence from China - Bin Dong; Benno Torgler (Center for Research in Economics, Management and the Arts (CREMA), 2010)
With complementary Chinese data sets and alternative corruption measures, we explore the consequences of corruption. Adopting a novel approach we provide evidence that corruption can have both, positive and negative effects, on economic development. The overall impact of corruption might be the balance of the two simultaneous effects within a specific institutional environment ("grease the wheels" and "sand the wheels"). Corruption is observed to considerably increase income inequality in China. We also find that corruption strongly reduces tax revenue. Looking at things from an expenditure point of view we observe that corruption significantly decreases government spending on education, R&D and public health in China. We also observe that regional corruption significantly reduces inbound foreign direct investment in Chinese regions, which indicates that the pollution haven hypothesis may not hold in China. This finding sheds a new light on the "China puzzle" that China is the largest developing host of FDI while it is appears to be very corrupt. Finally we observe that corruption substantially aggravates pollution probably through loosening environment regulation, and that it modifies the effects of trade openness and FDI on the stringency of environmental policy in a manner opposite to that observed in literature to date.
Keywords: D72; H11; K42; 330; Corruption; China; Government; Economic Development; Inequality; Environment